A comparison between level- and phase-shift space vector duty-cycle modulations using a nine-switch inverter for an ASD - N. Jarutus (2018)
© 2015 IEEE. In this paper, a comparison between the proposed level-shift and the phase-shift duty-cycle modulations, based on the continuous carrier-based space vector pulse width modulation (SVPWM) via the ac and dc components injection technique, is presented. The dual techniques are selected to overcome the output voltage distortion of the nine-switch inverter caused by the cross-over of the duty-cycle modulating signals, due to its existing shifted phase of the ac component and shifted level of the dc component. The mathematical models of the ac component injection design by the phase-shift technique and the dc component injection design by the proposed level-shift technique were analyzed to carry out the primary drawback avoidance, covering both variable frequency and constant frequency modes. Simulation results are executed on a dominant adjustable speed drive load cooperated with a standalone load to evaluate the dual techniques abilities, responding good dynamic- and steady-state performances.